Development and validation of single field multi-ion particle therapy treatments - Kopp, Benedikt; Mein, Stewart; Dokić, Ivana; Harrabi, Semi B.; Böhlen, Till Tobias; Haberer, Thomas; Debus, Jürgen; Abdollahi, Amir; Mairani, Andrea (International journal of radiation oncology, biology, physics, 2020)
Purpose To develop and validate combined ion-beam with constant relative biological effectiveness (RBE) (CICR) particle therapy in single field arrangements for improved treatment efficacy, robustness, and normal tissue sparing. Methods and Materials The PRECISE (PaRticle thErapy using single and Combined Ion optimization StratEgies) treatment planning system was developed to investigate clinical viability of CICR treatments. Single-field uniform dose (SFUD) with a single ion (proton [p], helium [He], or carbon [C]) and CICR (C-p and C-He) treatments were generated for 3 patient cases with a clinically prescribed dose of 3 Gy (RBE) per fraction. Spread-out Bragg peak plans were irradiated in homogenous and clinical-like settings using an anthropomorphic head phantom. A dosimetric and biological verification of CICRC-p treatments using a murine glioma cell line (GL261) was performed. Results CICR treatment plans for the 3 patients presented highly uniform physical dose while reducing high dose-averaged linear energy transfer gradients compared with carbon ions alone. When considering uncertainty in tissue parameter (α/β)x assignment and RBE modeling, the CICRC-p treatment exhibited enhanced biophysical stability within the target volume, similar to protons alone. CICR treatments reduced dose to normal tissue surrounding the target, exhibiting similar or improved dosimetric features compared with SFUDHe. For both CICRC-p and SFUD treatments, measurements verified the planned dose in the target within ∼3%. Planned versus measured target RBE values were 1.38 ± 0.02 and 1.39 ± 0.07 (<1% deviation), respectively, for the CICRC-p treatment in heterogenous settings. Conclusions Here, we demonstrate that by combining 2 (or more) ions in a single field arrangement, more robust biological and more conformal dose distributions can be delivered compared with conventional particle therapy treatment planning. This work constitutes the first dosimetric and biological verification of multi-ion particle therapy in homogeneous as well as heterogenous settings.
Published online: October 11, 2019
Gesehen am 15.04.2020